Effects of heterochronic, non-myeloablative bone marrow transplantation on age-related behavioural changes in mice. (October 2020) - Lountzi, Dimitra; Henzel, Kristin; Jazbec, Katerina; Bano, Daniele; Krauss, Sybille; Rožman, Primož; Ehninger, Dan
Highlights: Prior work has shown that blood-borne factor derived from young animals can have rejuvenating potential when transferred to old organisms In addition to humoral factors, cell-based factors might have a role in mediating these effects We explored whether heterochronic, non-myeloablative bone marrow transplantation (BMT) affects aging-associated behavioural changes in mice We detected no obvious differences between old mice that had received young BMT and age-matched controls Our study shows that non-myeloablative, heterochronic BMT had limited effects on age-related behavioural and cognitive alterations in mice Abstract: Experiments using heterochronic parabionts, i.e. young and old animals connected surgically and hence developing a shared circulation, have shown that blood-borne factors, transferred from young to old mice and vice versa, play a role in influencing a range of health outcomes associated with advanced age. Previous work has explored the contributory role of plasma-derived factors in mediating such parabiotic effects, including those on aging-associated neural and behavioural impairments. Here, we wanted to identify possible influences that blood-borne cellular factors may have on age-related behavioural phenotypes. Towards this end, we subjected old BALB/c H-2 d mice to repetitive non-myeloablative bone marrow transplants (BMT) from young donor animals and assessed effects on behaviour and cognition. We detected expected age-related alterations in our behavioural assays but did not discern any obvious differences between old BMT mice and old control animals. Our study represents the first to look at possible behavioural and cognitive effects of heterochronic, non-myeloablative BMT. Future work should extend this study by including additional behavioural tests in the analysis, addressing whether beneficial effects of BMT may be detectable on other genetic backgrounds and reconciling our findings with those achieved by myeloablative BMT.